1994
DOI: 10.1016/0010-8545(94)80025-1
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectra of RMn(CO)3(α-diimine) (RH, CH3): a CASSCF/CCI comparative study of the lowest singlet excited states

Abstract: Electronic spectra of RMn(CO)sub3(alpha-diimine) (R=H,CHsub3): a CASSCF/CCI comparative study of the lowest singlet excited states Daniel, C.; Matsubara, T.; Stor, G.J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Quite recently, the spectroscopy, photophysics, and photochemistry of a series of complexes M(L)(CO) 3 (α-diimine) (M = Mn, Re), in which L represents a metal fragment or an alkyl group bound to the metal by a high-lying σ orbital, have been studied in detail. From these studies, it was concluded that mainly d π (M) → π*(α-diimine) (metal-to-ligand-charge-transfer: MLCT) transitions contribute to the absorption spectra, but that decay to the ground state and homolytic cleavage of the metal−L bond take place from a close low-lying σ M - L → π*(α-diimine) (sigma-bond-to-ligand-charge-transfer: 3 σπ* or 3 SBLCT) excited state. To rationalize the experimental data, a few theoretical investigations, based either on DFT calculations , or on accurate CASSCF/MR-CCI calculations, , have been performed. Recently, the potential energy curves corresponding to the 1 A‘ electronic ground state and to the low-lying 3 A‘ excited states have been computed for the model complex Mn(H)(CO) 3 (H-DAB) as a function of q a = [Mn−H] and q b = [Mn−CO ax ] under the C s symmetry constraint .…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, the spectroscopy, photophysics, and photochemistry of a series of complexes M(L)(CO) 3 (α-diimine) (M = Mn, Re), in which L represents a metal fragment or an alkyl group bound to the metal by a high-lying σ orbital, have been studied in detail. From these studies, it was concluded that mainly d π (M) → π*(α-diimine) (metal-to-ligand-charge-transfer: MLCT) transitions contribute to the absorption spectra, but that decay to the ground state and homolytic cleavage of the metal−L bond take place from a close low-lying σ M - L → π*(α-diimine) (sigma-bond-to-ligand-charge-transfer: 3 σπ* or 3 SBLCT) excited state. To rationalize the experimental data, a few theoretical investigations, based either on DFT calculations , or on accurate CASSCF/MR-CCI calculations, , have been performed. Recently, the potential energy curves corresponding to the 1 A‘ electronic ground state and to the low-lying 3 A‘ excited states have been computed for the model complex Mn(H)(CO) 3 (H-DAB) as a function of q a = [Mn−H] and q b = [Mn−CO ax ] under the C s symmetry constraint .…”
Section: Introductionmentioning
confidence: 99%